A comparison of four different imaging modalities – Conventional, cross polarized, infra-red and ultra-violet in the assessment of childhood bruising. (October 2018) - Trefan, L.; Harris, C.; Evans, S.; Nuttall, D.; Maguire, S.; Kemp, A.M.
Abstract: Background: It is standard practice to image concerning bruises in children. We aim to compare the clarity and measurements of bruises using cross polarized, infra-red (IR) and ultra-violet (UV) images to conventional images. Methods: Children aged <11 years with incidental bruising were recruited. Demographics, skin and bruise details were recorded. Bruises were imaged by standard protocols in conventional, cross-polarized, IR and UV lights. Bruises were assessed in vivo for contrast, uniformity and diffuseness, and these characteristics were then compared across image modalities. Color images (conventional, cross polarized) were segmented and measured by ImageJ. Bruises of grey scale images (IR, UV) were measured by a 'plug in' of ImageJ. The maximum and minimum Feret's diameter, area and aspect ratio, were determined. Comparison of measurements across imaging modalities was conducted using Wilcoxon rank sum tests and modified Bland-Altman graphs. Significance was set at p < 0.05. Results: Twenty five children had 39 bruises. Bruises that were of low contrast, i.e. difficult to distinguish from surrounding skin, were also more diffuse, and less uniformity in vivo. Low contrast bruises were best seen on conventional and cross-polarized images and less distinctive on IR and UV images. Of the 19 bruises visible in all modalities, the only significant difference was maximum and minimum Feret's diameters and area were smaller on IR compared to conventional images. Aspect ratios were not affected by the modality. Conclusions: Conventional and cross-polarized imaging provides the most consistent bruise measurement, particularly in bruises that are not easily distinguished from surrounding skin visually. Highlights: Diffuse bruises may be measured on conventional & cross polarized imaging. Infrared or ultraviolet imaging may not show bruises which are difficult to see in vivo. Measurements of bruises using infrared imaging may be smaller than other modalities.